Treating connective tissue disease-associated interstitial lung disease: think outside the box : a perspective - Khor, Yet H.; Moor, Catharina C.; Merkt, Wolfgang; Buschulte, Katharina; Zheng, Boyang; Müller, Veronika; Kreuter, Michael (European respiratory review, 2025)
Connective tissue disease-associated interstitial lung disease is one of the most common subtypes of interstitial lung disease, which is a leading cause of morbidity and mortality in patients with these systemic autoimmune rheumatic diseases. A spectrum of disease trajectories exists within individual and across different connective tissue diseases. In individuals with connective tissue diseases who are at risk or at the early asymptomatic stage with interstitial lung changes, we have potential windows of opportunity for interventions to prevent the development of or progression to interstitial lung disease. In this perspective, we use systemic sclerosis and rheumatoid arthritis as sample cases to discuss emerging knowledge on disease pathogenesis, as well as to apply the preventative medicine concept for pharmacotherapeutic approaches at different disease stages of connective tissue disease-associated interstitial lung disease.